The benefits and threats of blockchain technology in healthcare: A scoping review - Israa Abu-elezz (17058009) (2020)
Background The application of blockchain technology is being explored to improve the interoperability of patient health information between healthcare organisations while maintaining the privacy and security of data. Objectives The objective of this scoping review is to explore and categorise the benefits and threats of blockchain technology application in a healthcare system. Methods Databases such as PubMed, CINAHL, IEEE, Springer, and ScienceDirect were searched using a combination of terms related to blockchain, healthcare, benefits and threats. Backward-reference list checking was conducted to identify other relevant references. Study selection process was performed in three steps based on PRISMA flow diagram. Extracted data were synthesised and presented narratively using tables and figures. Results The search resulted in 84 relevant studies that have been conducted of which only 37 unique studies were included in this review. Eight benefits of blockchain were categorised in either patient related-benefits (security and authorisation, personalised healthcare, patients' health data tracking, and patient’s health status monitoring) or organisational-related benefits (health information exchange, pharmaceutical supply chain, clinical trials, and medical insurance management). Meanwhile, eight threats of blockchain were categorised into three groups: organisational threats (installation and transaction costs, interoperability issues, and lack of technical skills), social threats (social acceptance and regulations issues), and technological threats (scalability issues, authorisation and security issues, high energy consumption, and slow processing speeds). Conclusion Blockchain is a viable technology that can improve the healthcare data sharing and storing system owing to its decentralisation, immutability, transparency and traceability features. However, many healthcare organisations remain hesitant to adopt blockchain technology due to threats such as security and authorisation issues, interoperability issues and lack of technical skills related to blockchain technology. Other Information Published in: International Journal of Medical Informatics License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.ijmedinf.2020.104246